Programming languages and systems 20th European symposium on programming, ESOP 2011, held as part of the joint European conferences on theory and practice of software, ETAPS 2011, Saarbrücken, Germany, March 26-April 3, 2011 : proceedings - Barthe, Gilles (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 20th European Symposium on Programming, ESOP 2011, held in Saarbrücken, Germany, March 30-April 1, 2011, as part of ETAPS 2011, the European Joint Conferences on Theory and Practice of Software. The 24 revised full papers presented together with one full length invited talk were carefully reviewed and selected from 93 full paper submissions. Papers were invited on all aspects of programming language research including: programming paradigms and styles, methods and tools to write and specify programs and languages, methods and tools for reasoning about programs, methods and tools for implementation, and concurrency and distribution.